2010
DOI: 10.1111/j.1556-4029.2010.01581.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Arsenic Poisoning: Clinical, Toxicological, Histopathological, and Forensic Features

Abstract: This report describes a suicide case by acute arsenic intoxication via intravenous injection. A 30-year-old woman injected arsenic As (V) (sodium arseniate disodique: Disodium Hydrogena Arsenik RP) in a successful suicide attempt. Three hours following administration, the woman developed severe digestive symptoms. She was admitted to a hospital and transferred to the intensive care unit within 12 h of the massive administration of arsenic. Despite therapeutic efforts, over the next 2 h she developed multiorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 18 publications
(32 reference statements)
2
28
0
8
Order By: Relevance
“…The results showed that ATO exposure increased the lung water content ratio significantly, and the degree and duration of increase were exposure concentration‐dependent. Similarly, Tournel et al () found that acute ATO poisoning causes hemorrhagic pulmonary edema. Presumably, because As is in group 15 (Va) of the periodic table, during energy metabolism, As affects the formation of high‐energy phosphate bonds, thereby hindering cell energy metabolism.…”
Section: Discussionmentioning
confidence: 85%
“…The results showed that ATO exposure increased the lung water content ratio significantly, and the degree and duration of increase were exposure concentration‐dependent. Similarly, Tournel et al () found that acute ATO poisoning causes hemorrhagic pulmonary edema. Presumably, because As is in group 15 (Va) of the periodic table, during energy metabolism, As affects the formation of high‐energy phosphate bonds, thereby hindering cell energy metabolism.…”
Section: Discussionmentioning
confidence: 85%
“…The liver is one of the primary targets for acute arsenic toxicity in vivo 4528. We examined plasma markers for liver injury, aspartate aminotransferase (AST) and alanine aminotransferase (ALT).…”
Section: Resultsmentioning
confidence: 99%
“…There are many Chinese patent medicines, such as Niuhuang Jiedu Wan , Jufang Zhibao San , Fufang Qingdai Pian , Angong NiuHuang San , Wansheng Huafeng Dan , among others, containing realgar [90–92]. Because they contain a large dose of realgar, these medicines showed high toxicity and obvious gastrointestinal tract irritation in clinic [93]. Replacement of realgar with RBS in prescriptions will reduce the application of realgar, leading to better control of the concentration of.…”
Section: The Antitumor Effect and Application Of Realgar Bioleaching mentioning
confidence: 99%